2006
DOI: 10.1002/chem.200501325
|View full text |Cite
|
Sign up to set email alerts
|

Triplet MLCT Photosensitization of the Ring‐Closing Reaction of Diarylethenes by Design and Synthesis of a Photochromic Rhenium(I) Complex of a Diarylethene‐Containing 1,10‐Phenanthroline Ligand

Abstract: Synthesis of the diarylethene-containing ligand L1 based on Suzuki cross-coupling reaction between thienyl boronic acid and the dibromophenanthroline ligand is reported. On coordination to the rhenium(I) tricarbonyl complex system, the photochromism of L1 could be photosensitized and consequently extended from intraligand excitation at lambda< or =340 nm in the free ligand to metal-to-ligand charge-transfer (MLCT) excitation at lambda< or =480 nm in the complex. The photochromic reactions were studied by (1)H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(80 citation statements)
references
References 70 publications
5
75
0
Order By: Relevance
“…The 1 H NMR spectrum of each of the DTE derivatives shows only a single set of signals, indicating that the compounds take antiparallel geometry or rapid interconversion of the two conformers occurs. 43 Recently, we studied the photoswitching of TTA upconversion with DTE derivatives, but that approach is based on the mixture of the three components. 47b Herein, for the first time a covalently connected DTE-photosensitizer dyad/triad was studied for TTA upconversion.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR spectrum of each of the DTE derivatives shows only a single set of signals, indicating that the compounds take antiparallel geometry or rapid interconversion of the two conformers occurs. 43 Recently, we studied the photoswitching of TTA upconversion with DTE derivatives, but that approach is based on the mixture of the three components. 47b Herein, for the first time a covalently connected DTE-photosensitizer dyad/triad was studied for TTA upconversion.…”
Section: Resultsmentioning
confidence: 99%
“…This kind of "intramolecular sensitization" of intraligand photochemistry by MLCT excitation, [13,[36][37][38][39][40][41] the kinetics of which were first determined [23] for [ReA C H T U N G T R E N N U N G (stpy)(CO) 3 A C H T U N G T R E N N U N G (bpy)] + , opens interesting possibilities in designing new molecular photonic switches and sensors. [11] Herein, we introduce these photoreactive properties in two new complexes [Re(Cl)(CO) 3 Figure 1) and investigate their redox properties, photochemistry, and excited-state dynamics. The excited complexes may undergo a trans!cis isomerization of the C=C bond, ILET with the oxidizing methylpyridinium ring, or just a simple radiative or nonradiative decay to the ground state, raising important questions about the factors controlling the photonic behavior of these multifunctional chromophores.…”
Section: A C H T U N G T R E N N U N G (Bpy)]mentioning
confidence: 99%
“…It will be demonstrated that the SO model accounts very well for absorption spectra, emission properties, and excited-state dynamics, some of its conclusions being qualitatively different from the spinfree approach. [Re(imH)(CO) 3 (phen)] + represents a broad class of Re I tricarbonyl-diimine complexes [21][22][23], which show very rich photophysics and photochemistry [10,14,15,24] and engage in a range of photonic applications such as photosensitizers and phototriggers of electron-transfer reactions [11,[25][26][27][28][29], photocatalysts of CO 2 reduction [30][31][32], phosphorescent labels and probes of biomolecules [33][34][35][36], sensors [37,38], molecular switches [39][40][41][42] and OLED emitters [43], or probes of ps-ns dynamics of solvents, proteins or supramolecular hosts [11,24,50,51,[63][64][65]. The chosen example [Re(imH)(CO) 3 (phen)] + [44] not only epitomizes the salient features of Re I carbonyl-diimine photophysics but also has a prominent position amongst Re-based photosensitizers because of its ability to trigger photoinduced electron transfer and relaxation dynamics in Re-labeled proteins [11,25,[44]…”
Section: Introductionmentioning
confidence: 99%